The Caribbean under the radar? A scoping review of carbapenemase-producing Enterobacterales across the region - Saied Ali; Ansara Baig; Rajeev Peeyush Nagassar; Liam P. Burke; Fidelma Fitzpatrick; Deirdre Fitzgerald-Hughes (PLOS Global Public Health, 2026)
Carbapenemase-producing Enterobacterales (CPE) are a critical antimicrobial resistance (AMR) threat globally. The Caribbean region, despite its high global connectivity, varied healthcare infrastructure and rising antimicrobial use, remains underrepresented in CPE surveillance data. Our study aims to map and characterise the existing literature on CPE in the Caribbean, including bacterial species, carbapenemase types, detection methods, and epidemiological trends. A scoping review was conducted in accordance with PRISMA-ScR guidelines. MEDLINE, EMBASE, Cochrane CENTRAL and Web of Science were searched to 1 st July 2025 in addition to grey literature (policy documents, guidelines, websites). Studies were included if they reported carbapenemase production among Enterobacterales from human, animal, or environmental sources in Caribbean nations (defined geophysically). Non-Caribbean studies and non-Enterobacterales organisms were excluded. Fourteen studies published between 2008 and 2024 met inclusion criteria. Reports originated from six countries: Cuba, Puerto Rico, Jamaica, Guadeloupe, the Dominican Republic, and Curaçao. Klebsiella pneumoniae was the most frequently reported species. The most common carbapenemase enzymes were KPC (including KPC-2 and KPC-8), NDM-1, NDM-5 and OXA-48. Co-production of NDM and KPC was documented. Detection was largely hospital-based, though community and environmental isolates were also identified. High levels of AMR were observed, with colistin often the only active agent. Surveillance gaps are evident across many populous Caribbean nations. CPE are established in multiple Caribbean countries, but surveillance remains irregular and limited. Addressing critical gaps in diagnostic capacity, reporting and molecular surveillance is essential to ensure the region’s inclusion in the global AMR response.